Analisis produktivitas tenaga kerja sektor pertanian di Sumatera - Awina Oktavia; Zulfanetti Zulfanetti; Yulmardi Yulmardi (Jurnal Paradigma Ekonomika, 2017)
The aims of this study was to analyze the effect of education and the exchange rate of farmers on the level of labor productivity in the agricultural sector in Sumatra. The data used is panel data of provinces in Sumatra during 2010-2014. The analysis used a panel data regression model. The results showed that education had significant positive effect, while the farmer exchange rate had a significant negative effect on the level of agricultural sector labor productivity in Sumatra.